2021
DOI: 10.1111/gcb.15988
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon stocks in temperate grasslands differ strongly across sites but are insensitive to decade‐long fertilization

Abstract: Copyright statement: This manuscript has been authored by UT-Battelle, LLC, under contract no. DE-AC05-00OR22725 with the US Department of Energy (DOE). The US government retains and the publisher, by accepting the article for publication, acknowledges that the US government retains a nonexclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for US government purposes. DOE will provide public access to these results of federal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 139 publications
4
36
2
Order By: Relevance
“…By contrast, larger slowly decomposing litter fractions could promote he accumulation of particulate organic matter (POM) and total SOM (Cotrufo et al, 2015). Interestingly, a study conducted in nine North American NutNet sites found no effects of N on MAOM or POM (Keller et al, 2022), raising uncertainty about whether differential effects of N over the course of litter decomposition have consistent consequences for SOM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, larger slowly decomposing litter fractions could promote he accumulation of particulate organic matter (POM) and total SOM (Cotrufo et al, 2015). Interestingly, a study conducted in nine North American NutNet sites found no effects of N on MAOM or POM (Keller et al, 2022), raising uncertainty about whether differential effects of N over the course of litter decomposition have consistent consequences for SOM.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of N deposition on grassland C cycling will likely depend on the supplies of other nutrients, since NPP in grasslands is often co‐limited by multiple nutrients, with N limitation more prevalent at higher latitudes (Cleland et al, 2019; Du et al, 2020; Fay et al, 2015). On the other hand, grassland surface soil C stocks are relatively insensitive to N and P addition, with strong but unexplained response variability across sites (Crowther et al, 2019; Keller et al, 2022), but increase with short‐term addition of K with micronutrients (Crowther et al, 2019). This inconsistency between nutrient effects on plant biomass production (NPP) and soil C accumulation indicates a gap in understanding of nutrient effects on litter and soil organic matter (SOM) decomposition across diverse grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, N has the potential to influence grassland C accumulation by concurrently changing plant biomass, detritus, and rates of decomposition. Adding N alone can have positive, negative, and neutral effects on soil C (e.g., Crowther et al, 2019; Keller et al, 2021), even when N increases aboveground plant biomass accumulation (Fay et al, 2015) and reduces the rate of litter and soil organic matter (SOM) decomposition (Gill et al, 2021; e.g., Riggs et al, 2015; Riggs & Hobbie, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Grasslands are crucial areas for SOM storage, covering 30-40% of the global land surface (Reynolds 2005;Petri et al 2009) and storing 16% of global soil C (Anderson 1991). Previous research has revealed that grassland SOM C is affected by nutrient availability, depending on environmental conditions (Yue et al 2017;Crowther et al 2019;Keller et al 2021). However, investigating SOM C and N coupling and distribution between functionally different pools of SOM can provide new insight for soil responses to global change, such as model constraints for microbial metabolism or vulnerability of soil C to warming (Buchkowski et al 2019;Rocci et al 2021).…”
Section: Introductionmentioning
confidence: 99%